Seasonal distribution of production of Apennine grasslands described from sward height - Bagella S.; Roggero P.P. (L'évolution des systèmes de production ovine et caprine : avenir des systèmes extensifs face aux changements de la société, 2004)
In the Apennine region, grassland grazing is at the root of the livestock system. It is essential to maintain the current level of biodiversity and to create the conditions for the development of the local rural society. This paper presents a simplified integrated approach between botany and agronomy to characterise the grassland space-time production pattern, based on the grazed sward height (SH) compared to a reference 28-day cutting interval, measured on well characterised pastoral facies. In this context, SH proved to be an effective indicator of herbage productivity, particularly to assess the time-space yield dynamics, which is relevant to rangeland management. SH measurements are quick and allow the estimate of grassland production on more sampling areas than destructive methods. This information can be used to support the space-time organisation of infrastructures and activities in the rangeland, to achieve a sustainable balance between grass production and animal grazing.
Séminaire du Sous-Réseau Systèmes de Production du Réseau Coopératif Interrégional FAO-CIHEAM de Recherche et Développement sur les Ovins et les Caprins, 2002/04/04-06, Alghero (Italy)